2014
DOI: 10.1002/mc.22102
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate modulates antioxidant enzyme expression in malignant and non‐malignant human colon tissues

Abstract: The induction of antioxidant enzymes is an important mechanism in colon cancer chemoprevention, but the response of human colon tissue to butyrate, a gut fermentation product derived from dietary fiber, remains largely unknown. Therefore, our study investigated the effect of a butyrate treatment on catalase (CAT) and superoxide dismutase (SOD2) in matched human colon tissues of different transformation stages (n = 3-15 in each group) ex vivo. By performing quantitative real-time PCR, Western blot, and spectrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 56 publications
0
23
0
2
Order By: Relevance
“…Former studies indicated that the induction of these genes can be attributed to butyrate as the key fermentation product of dietary fiber. 28,35,41,42 Though there is no direct link between the daily recommended nut intake and FS used in the present study, we could recently confirm that the fermentation of nuts results in up to 2.8-fold higher concentrations of short chain fatty acids compared to the control and a shift of molar ratios towards butyrate production ranging in physiological observed FIGURE 3 Growth inhibiting of LT97 colon adenoma cells after incubation with fermented nut samples and controls (blank, Synergy1®) in concentrations of 2.5-20% for 24 h (a), 48 h (b), and 72 h (c) (mean + SD, n = 3). Significant differences between blank and fermentation supernatants (FS) of Synergy1® or nuts (***P ≤ 0.001, **P ≤ 0.01, *P ≤ 0.05) and between FS ( a-e P ≤ 0.05, equal letters represent significant differences) were obtained by two-way Anova/Bonferroni post-test.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies indicated that the induction of these genes can be attributed to butyrate as the key fermentation product of dietary fiber. 28,35,41,42 Though there is no direct link between the daily recommended nut intake and FS used in the present study, we could recently confirm that the fermentation of nuts results in up to 2.8-fold higher concentrations of short chain fatty acids compared to the control and a shift of molar ratios towards butyrate production ranging in physiological observed FIGURE 3 Growth inhibiting of LT97 colon adenoma cells after incubation with fermented nut samples and controls (blank, Synergy1®) in concentrations of 2.5-20% for 24 h (a), 48 h (b), and 72 h (c) (mean + SD, n = 3). Significant differences between blank and fermentation supernatants (FS) of Synergy1® or nuts (***P ≤ 0.001, **P ≤ 0.01, *P ≤ 0.05) and between FS ( a-e P ≤ 0.05, equal letters represent significant differences) were obtained by two-way Anova/Bonferroni post-test.…”
Section: Discussionmentioning
confidence: 99%
“…Jahns et al [31] investigated the effect of a butyrate treatment on catalase and superoxide dismutase (SOD2) in matched human colon tissues of different transformation stages ex vivo. Despite a significantly lowered SOD2 transcript and to a lesser extent of protein level after butyrate exposure of normal colon cells, the catalytic activity was significantly enhanced, suggesting an increased protection against tissue superoxide radicals.…”
Section: Influence Of Butyrate On Anti-inflammation and Antioxidant Amentioning
confidence: 99%
“…Butyrate is responsible for a number of physiologic roles within the gastrointestinal tract, including maintenance of intestinal barrier integrity, regulation of epigenetic gene expression, and mediation of anti-inflammatory responses to oxidative stress [95][96][97]. Alterations of butyrate producing species have been noted in both UC and CD patients with somewhat differing roles.…”
Section: Genetic and Microbial Interactions In Inflammatory Bowel Dismentioning
confidence: 99%